A fluorescent penetration detection method and its application

By adding specific surfactant and secondary permeation steps to the fluorescence permeation detection method, the problem of penetration and emulsification time difference in traditional fluorescence permeation detection is solved, and efficient defect detection of metal workpieces such as aluminum alloys and titanium alloys is achieved, which improves the Sensitivity and reliability of detection.

CN115372253BActive Publication Date: 2024-12-20AVIC TEST GOLD STONE TESTING TECH (WUXI) CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202210816745.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-12
Publication Date
2024-12-20
Estimated Expiration
2042-07-12

AI Technical Summary

Technical Problem

Due to the large time difference between penetration and emulsification and imaging observation, traditional fluorescence penetration detection methods have reduced the flaw detection effect and cannot meet the precise detection requirements for internal defects of the product.

Method used

By using the steps of sonic cleaning, rinsing, drying, cooling, permeation, emulsification and imaging observation, the surfactant of specific types of hydroxypropyl di-starch phosphate and octylphenol polyoxyethylene ether are added to the penetrant. Improve the spreading ability and capillary climbing height of the permeate, reduce the time difference of permeate emulsification and imaging, and improve the defect effect through secondary permeation.

Benefits of technology

It significantly shortens the detection time and improves the imaging effect, allowing operators to clearly and effectively distinguish defects such as cracks, folding and cold separation on metal workpieces, improving detection sensitivity and reliability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to G01N21, and more specifically, to a fluorescent penetrant testing method and its application. The method is as follows: (1) ultrasonic cleaning; (2) rinsing and drying; (3) cooling and penetration; (4) spray rinsing; (5) imaging observation. The fluorescent penetrant testing method provided by the present invention is used to perform fluorescent penetrant testing on aluminum alloy, titanium alloy and other parts, so that operators can clearly and effectively distinguish defects such as cracks, folds, cold shuts, etc. The method has high sensitivity and good reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to G01N21, and more specifically, to a fluorescent penetration detection method and application thereof. Background Art

[0002] With the continuous development of modern manufacturing, people have higher demands for product quality, which also requires manufacturers to control the defects of parts more strictly. However, traditional flaw detection methods such as ultrasonic detection can no longer meet the needs of internal precise flaw detection.

[0003] Patent number CN1187603C provides an automatic flaw detection method using dye penetration method for crack detection. After the workpiece is treated with dye, it is detected and inspected with a camera, avoiding the problem of visual fatigue and missed detection caused by manual detection. Patent number CN113834801A provides a metal non-destructive flaw detection device, method and storage medium, which combines sensors, fluorescent signals and laser components, and matches the corresponding computer program. The detection equipment is small in size, making flaw detection more convenient while reducing costs.

[0004] However, although fluorescent flaw detection is constantly developing, the original magnified flaw detection effect is compromised due to the time requirements for penetration and emulsification and the large time difference between imaging observation and the original magnified flaw detection effect. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present invention provides a fluorescent penetrant detection method, which is as follows: (1) ultrasonic cleaning; (2) rinsing and drying; (3) cooling and penetration; (4) spray rinsing; (5) imaging observation.

[0006] As a preferred technical solution of the present invention, in the step (1), the ultrasonic cleaning is carried out by using an ultrasonic cleaning tank to clean the workpiece. The power of the ultrasonic cleaning tank is 5-7KW, the tank liquid temperature of the ultrasonic cleaning tank is 25-85°C; the frequency of the ultrasonic wave is 20-30KHz, and the cleaning time is 30-40min.

[0007] Through ultrasonic cleaning, oil, coolant and other contaminants on the surface of the workpiece are removed first, and the ultrasonic frequency and temperature are controlled to facilitate the penetration of subsequent penetrants.

[0008] As a preferred technical solution of the present invention, the material of the workpiece is aluminum alloy or titanium alloy.

[0009] As a preferred technical solution of the present invention, the rinsing is carried out through a rinsing tank, and pipes are provided at the bottom and periphery of the tank body of the rinsing tank. Holes are provided on the pipes, and compressed air is connected to the outside of the pipes. The pressure of the compressed air is 0.2-1Mpa.

[0010] As a preferred technical solution of the present invention, in the step (2), the rinsing time is 20-30 minutes, the drying time is 10-20 minutes, and the drying temperature is 140-160°C.

[0011] As a preferred technical solution of the present invention, the temperature during the infiltration in step (3) is 15-40°C, and the infiltration time is 7-9 minutes.

[0012] Preferably, a penetrant is added during the infiltration.

[0013] Preferably, the raw materials of the penetrant include 65-85 parts by weight of a solvent, 1-3 parts by weight of a dye, 1.3-2.5 parts by weight of a surfactant, 0.3-0.7 parts by weight of a wetting agent, and 20-35 parts by weight of a viscosity modifier.

[0014] Preferably, the solvent is deionized water and the dye is amaranth.

[0015] Preferably, the surfactant is selected from one or more of hydroxypropyl distarch phosphate, triethanolamine, fatty alcohol polyoxyethylene ether, and octylphenol polyoxyethylene ether.

[0016] Preferably, the surfactant is hydroxypropyl distarch phosphate and octylphenol polyoxyethylene ether.

[0017] The HLB value of octylphenol polyoxyethylene ether is 14-15.

[0018] Further preferably, in the surfactant, the weight ratio of hydroxypropyl distarch phosphate to octylphenol polyoxyethylene ether is (0.3-0.95):1.5.

[0019] In order to reduce the time difference between penetration emulsification and development, to improve the development effect. Through a large number of experiments, the applicant found that adding a specific type of hydroxypropyl distarch phosphate and a surfactant of octylphenol polyoxyethylene ether in the penetrant can not only improve the above-mentioned problems, reduce the time difference between penetration emulsification and development, improve the development effect, especially improve the spreading ability and capillary climbing height of the penetrant, but also unexpectedly reduce the corrosiveness to the workpiece. The applicant speculates that the main chain of octylphenol polyoxyethylene ether and fatty alcohol polyoxyethylene ether can interact with the cross-linked network structure of hydroxypropyl distarch phosphate, and promote the formation of intramolecular hydrogen bonds at the same time. Under the action of 1,2-propylene glycol, the surface tension and fluidity of the penetrant system are improved, and the contact angle between the surface of the penetrant molecule and the surface of the aluminum alloy or titanium alloy material is affected, thereby improving the penetration ability of the dye at the crack of the metal workpiece, resulting in the improvement of the development effect and the shortening of the process time. Compared with the time of 10-15min usually required for penetration on the market, the time in the present invention is greatly shortened.

[0020] The wetting agent is fatty alcohol polyoxyethylene ether and the viscosity regulator is 1,2-propylene glycol.

[0021] Preferably, the hydroxyl value of the fatty alcohol polyoxyethylene ether is 85-110 and the HLB value is 12-14.

[0022] The preparation method of the penetrant is as follows: various raw materials are mixed according to weight parts.

[0023] As a preferred technical solution of the present invention, the step (3) also includes emulsification, and the emulsification time is 40-70s.

[0024] Preferably, step (3) comprises cooling, infiltration and emulsification. During the emulsification, a penetrant is added.

[0025] Through secondary penetration, the penetration of the penetrating liquid on the surface defects of the workpiece is further enhanced, thereby amplifying the defect effect and making the phenomenon results easier to observe.

[0026] As a preferred technical solution of the present invention, the step (5) specifically comprises spraying the developing powder on the workpiece processed in the step (4).

[0027] As a preferred technical solution of the present invention, the developing temperature is 25-40°C.

[0028] In the developing tank, the compressed air after the developer powder is filtered by the oil-water separator is blown into the powder barrel to generate a "powder explosion". The "powder explosion" is blown into the tank body by a pneumatic negative pressure generator, so that the developer powder instantly fills the developing tank, which can make the developer powder fully atomized and evenly distributed to form a uniform film on the surface of the parts and cover the base color of the parts with low powder consumption.

[0029] Preferably, the phenomenon in step (5) is observed in a dark room. A suspended black light filter is set above the inspection table in the dark room, and the initial measurement value of the black light intensity at 38cm from the black light filter is not less than 4000μW / cm 2 When observing defects, use a handheld black light filter. The initial measurement value of the black light intensity at 38cm from the handheld black light filter is not less than 8000μW / cm 2 .

[0030] A second aspect of the present invention provides an application of a fluorescent penetration testing method in detecting surface defects of metal workpieces.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] Adding a specific type of surfactant of hydroxypropyl distarch phosphate and octylphenol polyoxyethylene ether to an aqueous penetrant, wherein the weight ratio of hydroxypropyl distarch phosphate and octylphenol polyoxyethylene ether is (0.3-0.95):1.5, can not only reduce the time difference between penetration emulsification and imaging, improve the imaging effect, especially improve the spreading ability and capillary climbing height of the penetrant, but also reduce the corrosiveness to the workpiece. The fluorescent penetrant detection method provided by the present invention is used to perform fluorescent penetrant detection on aluminum alloy, titanium alloy and other parts, so that the operator can clearly and effectively distinguish defects such as cracks, folds, cold shuts, etc., and the method has high sensitivity and good reliability. DETAILED DESCRIPTION

[0033] Example

[0034] The workpiece in the embodiment is sourced from AVIC Touchstone Testing Technology (Wuxi) Co., Ltd., amaranth is purchased from Jizhi Reagent, CAS No. 915-67-3, hydroxypropyl distarch phosphate is CAS No. 53124-00-8, octylphenol polyoxyethylene ether is purchased from Qingtianyu, HLB value is 14.5, fatty alcohol polyoxyethylene ether is purchased from BASF, model AEO-9, hydroxyl value is 90-100, HLB value is 13, and imaging powder is purchased from American Magnetic Flux, model ZP-4B.

[0035] Example 1

[0036] This example provides a fluorescent penetrant testing method, which is as follows: (1) ultrasonic cleaning; (2) rinsing and drying; (3) cooling, penetration, and emulsification; (4) spray rinsing; and (5) imaging observation.

[0037] In step (1), the ultrasonic cleaning is performed by using an ultrasonic cleaning tank to clean the workpiece. The power of the ultrasonic cleaning tank is 6KW, the temperature of the tank liquid is 55°C, the frequency of the ultrasonic wave is 25KHz, and the cleaning time is 35min.

[0038] The material of the workpiece is titanium alloy.

[0039] Rinsing is carried out through a rinsing tank, the bottom and periphery of which are provided with pipes, holes are provided on the pipes, and compressed air is connected to the outside of the pipes, and the pressure of the compressed air is 0.5Mpa.

[0040] In step (2), the rinsing time is 25 minutes, the drying time is 15 minutes, and the drying temperature is 150°C.

[0041] The temperature during the infiltration in step (3) is 35° C. and the infiltration time is 8 min.

[0042] Penetrant is added during penetration.

[0043] The raw materials of the penetrant include 72 parts by weight of a solvent, 1.6 parts by weight of a dye, 1.85 parts by weight of a surfactant, 0.45 parts by weight of a wetting agent, and 27.1 parts by weight of a viscosity modifier.

[0044] The solvent is deionized water and the dye is amaranth.

[0045] The surfactant is hydroxypropyl distarch phosphate and octylphenol polyoxyethylene ether. In the surfactant, the weight ratio of hydroxypropyl distarch phosphate and octylphenol polyoxyethylene ether is 0.35:1.5.

[0046] The wetting agent is fatty alcohol polyoxyethylene ether and the viscosity regulator is 1,2-propylene glycol.

[0047] The preparation method of the penetrant is as follows: various raw materials are mixed according to weight parts.

[0048] Emulsification time: 50s. During emulsification, add penetrant.

[0049] Step (5) specifically involves spraying the developing powder onto the workpiece processed in step (4).

[0050] The developing temperature is 30°C.

[0051] Step (5) Observe in a dark room after the phenomenon. A suspended black light filter is set above the inspection table in the dark room. The initial measurement value of the black light intensity at 38cm from the black light filter is 5000μW / cm 2 When observing defects, a handheld black light filter is used. The initial measurement value of the black light intensity at 38cm from the handheld black light filter is 8500μW / cm 2 .

[0052] Example 2

[0053] This example provides a fluorescent penetrant detection method. Different from Example 1, the raw materials of the penetrant include 70 parts by weight of solvent, 1.1 parts by weight of dye, 1.75 parts by weight of surfactant, 0.4 parts by weight of wetting agent and 22 parts by weight of viscosity modifier. Among the surfactants, the weight ratio of hydroxypropyl distarch phosphate and octylphenol polyoxyethylene ether is 0.35:1.5.

[0054] Example 3

[0055] This example provides a fluorescent penetrant detection method. Different from Example 1, the raw materials of the penetrant include 81 parts by weight of solvent, 2.4 parts by weight of dye, 2.3 parts by weight of surfactant, 0.6 parts by weight of wetting agent and 35 parts by weight of viscosity modifier. Among the surfactants, the weight ratio of hydroxypropyl distarch phosphate and octylphenol polyoxyethylene ether is 0.8:1.5.

[0056] Example 4

[0057] This example provides a fluorescent penetrant detection method. Different from Example 1, the raw materials of the penetrant include 75 parts by weight of solvent, 1.5 parts by weight of dye, 2 parts by weight of surfactant, 0.5 parts by weight of wetting agent and 30 parts by weight of viscosity modifier. Among the surfactants, the weight ratio of hydroxypropyl distarch phosphate and octylphenol polyoxyethylene ether is 1:1.

[0058] Example 5

[0059] This example provides a fluorescent penetrant testing method. The difference from Example 1 is that in step (1), the ultrasonic cleaning is carried out by using an ultrasonic cleaning tank to clean the workpiece. The power of the ultrasonic cleaning tank is 7KW, the tank liquid temperature of the ultrasonic cleaning tank is 60°C; the frequency of the ultrasonic wave is 25KHz, and the cleaning time is 40 minutes.

[0060] In step (2), the rinsing time is 20 minutes, the drying time is 20 minutes, and the drying temperature is 140°C.

[0061] The temperature during the infiltration in step (3) is 45° C. and the infiltration time is 5 min.

[0062] Performance Testing:

[0063] 1. Performance test of permeate: add 10 mL of permeate obtained in Example 1-4 to an acid burette, place a 60 mm diameter watch glass below the burette, and control the distance between the lower port of the burette and the bottom of the watch glass to be 35 mm. Add the permeate drop by drop to the watch glass until it just covers the bottom of the watch glass, and record the sample volume used at this time, which is the spreading volume; place one end of a glass capillary with ventilation at both ends and an inner diameter of 0.9-1.1 mm in the permeate obtained in Example 1-4, and measure the height of the liquid level rise after the liquid level rises to a stable level, which is the capillary climbing height; use a surface tension meter to measure the surface tension of the permeate obtained in Example 1-4, and the results are shown in Table 1:

[0064] Table 1

[0065] Example Spreading volume (mL) Capillary climbing height (mm) Surface tension (mN / m) 1 7.6 13.4 41.28 2 7.4 13.1 40.06 3 7.0 13.1 38.35 4 4.5 9.2 27.64

[0066] 2. Sensitivity test: The fluorescent penetrant detection method of Examples 1-5 was tested according to HB Z61-1998. The results are shown in Table 2:

[0067] Table 2

[0068] Example Sensitivity 1 Level 4 2 Level 3 3 Level 4 4 Level 2 5 Level 2

Claims

1. A fluorescent penetrant detection method, It is characterized in that The method is as follows: (1) ultrasonic cleaning; (2) rinsing and drying; (3) cooling and penetration; (4) spray rinsing; (5) imaging observation; The temperature during penetration in step (3) is 15-40° C., and the penetration time is 7-9 min. A penetrant is added during the penetration, and the raw materials of the penetrant include 65-85 parts by weight of a solvent, 1-3 parts by weight of a dye, 1.3-2.5 parts by weight of a surfactant, 0.3-0.7 parts by weight of a wetting agent, and 20-35 parts by weight of a viscosity modifier; The surfactant is hydroxypropyl distarch phosphate and octylphenol polyoxyethylene ether. In the surfactant, the weight ratio of hydroxypropyl distarch phosphate and octylphenol polyoxyethylene ether is (0.3-0.95):1.

5.

2. The fluorescent penetrant detection method according to claim 1, It is characterized in that In the step (1), the ultrasonic cleaning is performed by using an ultrasonic cleaning tank to clean the workpiece. The power of the ultrasonic cleaning tank is 5-7KW, the temperature of the tank liquid is 25-85°C, the frequency of the ultrasonic wave is 20-30KHz, and the cleaning time is 30-40min.

3. The fluorescent penetrant detection method according to claim 2, It is characterized in that The workpiece is made of aluminum alloy or titanium alloy.

4. The fluorescent penetrant detection method according to claim 1, It is characterized in that The rinsing is carried out through a rinsing tank, the bottom and periphery of the tank body of the rinsing tank are provided with pipes, holes are provided on the pipes, and the outside of the pipes is connected to compressed air, and the pressure of the compressed air is 0.2-1Mpa.

5. The fluorescent penetrant detection method according to claim 4, It is characterized in that In the step (2), the rinsing time is 20-30 minutes, the drying time is 10-20 minutes, and the drying temperature is 140-160°C.

6. The fluorescent penetrant detection method according to claim 1, It is characterized in that The step (3) also includes emulsification, and the emulsification time is 40-70s.

7. The fluorescent penetrant testing method according to claim 1, It is characterized in that The step (5) specifically comprises spraying the developing powder onto the workpiece processed in the step (4).

8. The fluorescent penetrant testing method according to claim 7, It is characterized in that The developing temperature is 25-40°C.

9. Application of the fluorescent penetrant testing method according to any one of claims 1 to 8 in detecting surface defects of metal workpieces.

Citation Information

Patent Citations

  • Metal nondestructive flaw detection equipment and method and storage medium

    CN113834801A

  • Automatic error detection method used during crack inspection according to the dye penetration method

    CN1187603C

  • Fluorescent penetrant inspection system and method

    CN104165893A

  • Nondestructive testing method based on fluorescent permeation

    CN113075227A

  • High-temperature metal surface flaw detection method

    CN113447495A